Viewpoint,Not economy but extremism is threatening Europe's future - Bedrudin Brljavac, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
As the European Union focuses all attention and energy to confront its serious economic and financial crisis which is well nigh threatening its integration process, it would be unwise to sideline other equally potent forces of European disintegration such as political chauvinism and extremism. In fact, it is more important for the Europeans to manage cultural, national, and religious pluralisms than to focus all their energy on solving the current financial crisis.